Use of the World Health Organization Access, Watch, and Reserve Classification to Follow Trends in Prescription of Antibiotic Use in Two Pediatric Intensive Care Units in Rio de Janeiro, Brazil - Araujo da Silva, André Ricardo; Oliveira, Cristina Vieira de Souza; Teixeira, Cristiane Henriques; Leal, Izabel Alves (Journal of Pediatric Infectious Diseases, 2020)
Objective The recommended percentage of antibiotic use in pediatric intensive care units (PICUs) using the World Health Organization (WHO) Access, Watch, and Reserve (AWaRE) classification is not known.Methods We have conducted an interrupted time series analysis in two PICUs in Rio de Janeiro, Brazil, over a period of 18 months. The type of antibiotics used was evaluated using the WHO AWaRE classification, and the amount of antibiotic was measured using days of therapy/1,000 patient-days (DOT/1000PD) after implementation of an antimicrobial stewardship program (ASP). The first and last semesters were compared using medians and the Mann–Whitney's test. The trends of antibiotic consumption were performed using time series analysis in three consecutive 6-month periods.Results A total of 2,205 patients were admitted, accounting for 12,490 patient-days. In PICU 1, overall antibiotic consumption (in DOT/1000PD) was 1,322 in the first 6 months of analysis and 1,264.5 in the last 6 months (p = 0.81). In PICU 2, the consumption for the same period was 1,638.5 and 1,344.5, respectively (p = 0.031). In PICU 1, the antibiotics classified in the AWaRE groups were used 33.2, 57.9, and 8.4% of the time, respectively. The remaining 0.5% of antibiotics used were not classified in any of these groups. In PICU 2, the AWaRE groups corresponded to 30.2, 60.5, and 9.3% of all antibiotics used, respectively. There was no use of unclassified antibiotics in this unit. The use of all three groups of WHO AWaRE antibiotics was similar in the first and the last semesters, with the exception of Reserve group in PICU 2 (183.5 × 92, p = 0.031).Conclusion A significant reduction of overall antibiotic use and also in the Reserve group was achieved in one of the PICU units studied. The antibiotics classified in the Watch group were the most used in both units, representing ∼60% of all the antibiotics consumed.
Keywords: pediatric; intensive care unit; antibiotic